If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1t + 5 = 2t Reorder the terms: 5 + 1t = 2t Solving 5 + 1t = 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. 5 + 1t + -2t = 2t + -2t Combine like terms: 1t + -2t = -1t 5 + -1t = 2t + -2t Combine like terms: 2t + -2t = 0 5 + -1t = 0 Add '-5' to each side of the equation. 5 + -5 + -1t = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1t = 0 + -5 -1t = 0 + -5 Combine like terms: 0 + -5 = -5 -1t = -5 Divide each side by '-1'. t = 5 Simplifying t = 5
| 13.99(x-12)=07.93 | | y+9=13.5 | | 2(y+5)=8y+28 | | -(-8y+6z-7)= | | 2p-1=5p-10 | | 8z+22+13z=71 | | 9a=-9a^2-18 | | 11w=3740 | | 5+4*8= | | 14+(17+b)= | | 1+lx+1= | | 8x+14=126 | | 5(9g+2)=50 | | 2a=a+40 | | cos(3x-20)=sin(5x+6) | | f-1=-3x^2+2x-7 | | 8q^2+4q=7q^2-2q+27 | | 13d+6=6d+27 | | 3(x-9)=-10.8 | | 3(x-9)=10.8 | | 7(a+5)=73.5 | | y-54=7t | | X^2+12x-9= | | 43.2=6c-9 | | an=15+3(n-3) | | 7e-1=15.8 | | -10x+9y=11 | | 6x^4-12x^3=0 | | 3p=29.1 | | h-25=36 | | 3k+2(3k+2)=49 | | 2x+12+38=80 |